The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s00056-016-0046-0
|View full text |Cite
|
Sign up to set email alerts
|

Enamel shear bond strength of two orthodontic self-etching bonding systems compared to Transbond™ XT

Abstract: Using the two self-etching no-mix adhesives (Prompt L-Pop™ and Scotchbond™) for orthodontic appliances does not affect either the SBS or ARI scores in comparison with the commonly used total-etch system Transbond™ XT. In addition, Scotchbond™ Universal supports bonding on all types of surfaces (enamel, metal, composite, and porcelain) with no need for additional primers. It might therefore be helpful for simplifying bonding in orthodontic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 26 publications
2
33
0
Order By: Relevance
“…Some previous studies have reported a higher shear bond strength when the laser was used in the manufacture process of the bracket base. 6,[18][19][20] On the other hand, it also has been shown no significant difference 21 or even lower SBS between laser structured bracket base and another type of bracket base. 6 The inconsistencies in the literature are mainly due to study designs (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies have reported a higher shear bond strength when the laser was used in the manufacture process of the bracket base. 6,[18][19][20] On the other hand, it also has been shown no significant difference 21 or even lower SBS between laser structured bracket base and another type of bracket base. 6 The inconsistencies in the literature are mainly due to study designs (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…High bond strength values are potentially dangerous to enamel and they could cause enamel fracture during debonding. 1,3,7,11,19,20 Although shear bond strength test differs from tensile bond strength, the literature has referenced the potential enamel damage to tensile bond strength as low as 9.7 MPa. 11,26,27 However, authors agree that the values of the SBS obtained in vitro are above the acceptable values in vivo and could carry an increased risk of enamel fracture.…”
Section: Discussionmentioning
confidence: 99%
“…In the presented experiment, the Transbond XT was used in both test groups. It has been used in many studies, [18][19][20][21] so the results can be comparable. The bonding material Transbond SEP Plus has also been proven to be one of the best bonds used in orthodontics.…”
Section: Discussionmentioning
confidence: 99%
“…The Transbond products are one of the few (next to the Clearfil SE) materials that show an acceptable stress behavior under the thermocycling conditions, which can mimic the in vivo conditions. 20 Also, the risk of debonding-induced enamel defects is related to the bracket system used. 22 Therefore, only 1 bracket system has been used which was also used in earlier studies to get comparable results.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays direct bonding in orthodontic clinics is considered a regular technique. Many attempts to improve the performance of such procedures and reduce the technique sensitivity have been done including the utilization of self-etch primers, [1][2][3][4] one-step adhesives, 5 and different polymerization mode (chemical and light). [6][7][8] Several factors can potentially influence the bond strength between orthodontic brackets and enamel surface such as type of the adhesive system, composition and application time of the etchant, bracket's type and its base style.…”
Section: Introductionmentioning
confidence: 99%